ANALISIS VISUAL POSTINGAN FACEBOOK OKKA SUPARDAN: PENDORONG VIRALITAS OBJEK WISATA PANYAWEUYAN MAJALENGKA - Teddy Maulana Hidayat Sudirman; Atef Fahrudin; Adi Junadi; Restu Syahmagun Suryadi (Prodi Ilmu Komunikasi, FISIP, Universitas Muhammadiyah Cirebon, 2024)
This research aims to analyze the role of Okka Supardan's visual posts on Facebook in driving the virality of the Panyaweuyan Majalengka tourist attraction. Using a qualitative case study approach and visual analysis methods, the research examines the visual elements in the posts and analyzes the responses of Facebook users. The research findings indicate that consistent posting, the use of human interest elements, innovative photography techniques such as aerial photography, as well as aesthetic visual elements like captivating compositions, dramatic lighting, and contrasting colors contribute to the success in driving virality. The selection of the right time for taking photos, such as the golden hour and blue hour, also plays a crucial role. The research reveals Okka's role as a credible and influential local influencer in disseminating information about Panyaweuyan. Nevertheless, challenges such as the spread of inaccurate information and overtourism need to be managed through collaboration between tourism managers and influencers.